SURGICAL VS. CONSERVATIVE TREATMENT FOR DEGENERATIVE LUMBAR STENOSIS - Dias,Caio Roncon (2015)
Objectives:To compare the clinical outcomes between patients with degenerative lumbar stenosis who were treated by decompression with those awaiting the same kind of treatment for the disease.Methods:Retrospective study which divided patients with degenerative lumbar stenosis with surgical indication in 2 groups, operated and awaiting the procedure. The Oswestry Disability Index (ODI) questionnaire, visual analog scale and SF36 were applied.Results:Twelve operated patients and 18 awaiting the procedure were included. The average age of those operated was 59 years (43-70), and 55 (37-82) (p=0.3) for those awaiting surgery. The operated group had a mean ODI of 38.67 against 59.72 (p<0.05) in the non-operated group. The pain analog scale had lumbar result of 5.33 and pain radiating to the lower limbs of 3.83 in operated patients, against 6.78 (p>0.05) and 7.22 (p<0.05) in the awaiting surgery patients, respectively. As for the SF36 scale, functional capacity, limitations due to physical aspects and pain had an average score of 36.25, 19.58 and 21.67 in the operated group against 35.94, 27.50 and 32.61 in the awaiting group (p>0.05), respectively.Conclusion:The operated patients showed improvement of referred pain in the lower limbs (leg VAS) and improved function (Oswestry), however showed no significant change in quality of life according to SF36 scale and low back pain (lumbar VAS) were found.